Some Feedback about the Current National Curriculum - Malikova, Nargiza Bakhtiyorovna (Research Parks Publishing LLC, 2022)
In this article, the introduction of the National Curriculum, the advantages and conveniences of the curriculum, work on dictionaries in the textbooks